Analisis Strategi Penerjemahan dalam Terjemahan Dīwān al-Syāfi`ī - Pamungkas, Muhammad Ibnu; Akmaliyah, Akmaliyah (Adabiyyāt: Jurnal Bahasa dan Sastra, 2019)
This research aims to describe and analyze the strategy used in translating Dīwān al-Imām al-Syāfi`ī. All analyzed data were taken from the translation of Dīwān al-Imām al-Syāfi`ī using dynamic equivalence technique. The method used in conducting this research is distributional review, starting from describing, filtering, classifying, and analyzing the data. Analysis process starts from choosing the translation strategy used in translating the text, then classify each data based on the strategy. After that, the classified data is being analyzed by stating which strategy category is used and what would probably be the reason for the translator to chose that specific strategy. The result shows that there are four translation strategies used by the translator in translating Dīwān al-Imām al-Syāfi`ī. Those translation strategies are replacing words order (taqdīm wa ta’khīr), loss (inqāṣ), gain (ziyādah), and substitution (tabdīl). For loss and gain strategies, there are another two categories which are avertable and inavertable. Based on the result of the analysis, the researcher then conclude that the main reason for the translator in choosing to use these strategies is the presence of linguistic and non-linguistic differences. Linguistic difference is indicated at patterns of sentence, uslūb and the dilālah between the two languages. As for the non-linguistic difference is related with cultural differences between the two languages.